Adam Smith’s moral foundations of self-interest and ethical social order - Arevuo, Mikko (Wiley, 2023)
This article draws on textual evidence from The Theory of Moral Sentiments and The Wealth of Nations to address mistaken interpretations of Adam Smith's fundamental concept of self-interest as greed that has been said to have had a corrosive influence on markets, commercial behaviour, and widening inequality. To the contrary, Smith's complex set of human motivations, including self-interest, his economic system that is based on free markets, and institutional frameworks governing productive property rights and the rule of law are argued to increase aggregate wealth, improve the position of those least well off, and maintain ethical social order.
Keywords: Adam Smith; ethics; greed; impartial observer; inequality; moral philosophy; self-interest; sympathy; Theory of Moral Sentiments; Wealth of Nations